THE CRUCIAL ROLE OF SOCIAL WORKERS IN SUPPORTING STUDENTS WELL-BEING AND EDUCATION - Chriestine Lucia Mamuaya (KENDALI: Economics and Social Humanities, 2025)
School social workers hold a vital role in promoting students emotional, mental, and social well-being, which directly impacts their educational success. This study uses a literature review method to explore the functions, challenges, and opportunities faced by school social workers in Indonesia. Key findings show that social workers support students through mental health interventions, advocacy for disadvantaged students, collaboration with school staff, and addressing socio-economic issues. However, the profession faces significant barriers, including shortages of trained personnel, limited resources, especially in rural areas, and persistent social stigma. Despite these challenges, growing awareness about mental health and student welfare offers opportunities to strengthen the role of social workers in schools. The study recommends expanding the workforce of social workers, enhancing training, and fostering multi-stakeholder collaboration to improve service delivery and ensure equitable student support nationwide. Ultimately, the article emphasizes the need for comprehensive policies and systemic support to maximize the contributions of school social workers in enhancing students academic and personal development.